Desain Aplikasi Mobile Gamifikasi untuk Pramuka dengan Metode UI/UX - Putra Prakasa, S.T., M.Kom., Fedelis Brian (Universitas Atma Jaya Yogyakarta, 2021)
Abstract. The number of Scout members has decreased due to being outdone by other extracurriculars. In addition, given the current pandemic conditions, scouting activities are hampered. This study aims to create an attractive and online Scout mobile application prototype. This research method applies gamification so that scouting activities especially in schools, become more enjoyable and more attractive to students. Apart from gamification, this research also uses UI / UX methods such as usability testing, A / B testing, and User Experience Questionnaires (UEQ). This method is used so that the results of the prototype design can be easily used and understood by the user. The results of this study indicate that the gamification application in this prototype was successful. In addition, the design results that have been tested with the UI / UX method get a mean value of 2.04 and are included in the excellent criteria. Looking at the results of the research, it can be said that gamification makes scouting activities more interesting. Furthermore, the design concept of this application can help scouting activities online.Keywords: Gamification, Scout, UI/UX.Abstrak. Jumlah anggota pramuka mengalami penurunan dikarenakan kalah bersaing dengan ekstrakurikuler lainnya. Selain itu, mengingat kondisi pandemi saat ini, kegiatan pramuka menjadi terhambat. Penelitian ini bertujuan untuk membuat purwarupa aplikasi mobile pramuka secara daring dan menarik. Penelitian ini menerapkan gamifikasi agar kegiatan pramuka khususnya di sekolah menjadi lebih menarik minat siswa dan lebih menyenangkan. Selain gamifikasi, penelitian ini juga menggunakan metode UI/UX seperti usability testing, A/B testing dan User Experience Questionaire (UEQ). Metode ini digunakan agar hasil desain purwarupa dapat mudah digunakan dan dimengerti oleh pengguna. Penelitian ini menunjukan penerapan gamifikasi di purwarupa ini berhasil. Selain itu, hasil desain yang telah diuji dengan metode UI/UX mendapatkan nilai rerata 2,04 yang termasuk ke dalam kriteria unggul. Berdasar dari hasil penelitian, dapat dikatakan penggunaan gamifikasi membuat kegiatan pramuka lebih menarik. Selain itu, konsep desain aplikasi ini dapat membantu kegiatan pramuka secara daring.Kata Kunci: Gamifikasi, pramuka, UI/UX.